Annals of tropical medicine & parasitology - Liverpool School of Tropical Medicine (Academic Press, 2011)
"Liverpool School of Tropical Medicine. Scientific record; compiled by Dorothy Allmand" (a history of the school and of its activities): v. 15, 1921, p. [1]-47
Keywords: Tropical medicine : Periodicals; Trypanosomiasis : Periodicals; Parasites : Periodicals; Tropical medicine; Parasitic diseases; Parasitology; Parasites; Medical parasitology : Periodicals; Tropical Medicine; Parasitic Diseases; Parasitology; Parasites; Parasites : Périodiques; Parasitologie médicale : Périodiques; Médecine tropicale : Périodiques; Trypanosomiase : Périodiques; Médecine tropicale; Maladies parasitaires; Parasitologie; Medical parasitology; Trypanosomiasis; Tropische geneeskunde; Tropical & Arctic Medicine